Assessing the Drivers of Financial Distress in Indonesian Rattan SMEs through Digital and Financial Perspectives - Sudaryo, Yoyo; Hamdani, Deni; Sofiati, Nunung Ayu; Sipahutar, Dayan Hakim Natigor; Sutisna, Sutisna (Pandawan, 2025)
This study's objectives are to ascertain the impact of variables that determine financial distress among Small and Medium-sized Enterprises (SMEs) during the COVID-19 pandemic and post-pandemic period, including the perception of SMS offenders, knowledge of digital marketing, and growth in net profits, as well as to offer solutions to the issues that SMEs face. In Cirebon a descriptive and verifying strategy is taken in the employment of quantitative methodologies in the research. Primary data were used. Gathering information from fieldwork and library research based on surveys distributed and previously published works on SMS's Rattan crimes registered with Cirebon's Micro & Medium Enterprises Cooperation Service. Verification statistics analysis procedures include the use of hypothetical testing with partial and simultaneous tests (f and t-test) as well as data analysis testing using double linear regression. One hundred respondents from SME victim Rattan Cirebon provided the sample data. IBM SPSS version 21.0 is the analytical program that was utilized to process the data. According to some of the research findings, financial distress is greatly impacted by the impression of SME offenders, is unaffected by knowledge of digital marketing, and is greatly impacted by an increase in net profit. Simultaneous research findings reveal that the perspective of SME offenders, comprehension of digital marketing, and growth in net profit have a noteworthy impact on financial Distress.